Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1253/circj.cj-20-0024
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Recurrence After First-Ever Stroke in a General Population of 1.4 Million Japanese Patients ― The Shiga Stroke and Heart Attack Registry Study ―

Abstract: Background: Despite many effective strategies for the prevention of recurrent stroke, individuals who survive an initial stroke have been shown to be at high risk of recurrent stroke. The aim of this study was to investigate the current status of stroke recurrence after first-ever stroke using a population-based stroke registry in Japan. Methods and Results:As part of the Shiga Stroke and Heart Attack Registry, the Shiga Stroke Registry is an ongoing populationbased stroke registry study that covers approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…However, as the rate of stroke recurrence was higher in first two years of follow-up period, this may not substantially affect the final results. According to the previous studies from UK and Japan, they reported the proportions of 75% 11 and 92% 39 of those recurrent stoke patients who recurred within 2 years of follow-up since first stroke. Besides, there was 77% of recurrent stroke patients who recurred within first 3 years of follow-up among Chinese population 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, as the rate of stroke recurrence was higher in first two years of follow-up period, this may not substantially affect the final results. According to the previous studies from UK and Japan, they reported the proportions of 75% 11 and 92% 39 of those recurrent stoke patients who recurred within 2 years of follow-up since first stroke. Besides, there was 77% of recurrent stroke patients who recurred within first 3 years of follow-up among Chinese population 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Age was a prognostic indicator for mortality during admission in our study. Takashima et al analyzed clinical factors that increase the 2-year and 5-year mortality after stroke in the Japanese population of 1.4 million persons [ 12 , 13 ]. In their study, patients with subarachnoid hemorrhage were also enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, regarding mortality risk, five years after stroke onset, the post hemorrhagic stroke patients aged from 75 to 84 years and those aged 85 years old or more had a hazard ratio of 29.18 and 57.69, respectively, when compared to those aged less than 45 years old. The post-ischemic stroke patients aged 75 to 84 and those aged 85 years old or older had a hazard ratio of 15.67 and 37.03, respectively, when compared to those aged less than 45 years old [ 12 , 13 ]. In our study, the mean age of the patients in the non-survival group was 85.7 years old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations